2022
DOI: 10.1093/jac/dkab435
|View full text |Cite|
|
Sign up to set email alerts
|

A random survey of the prevalence of falsified and substandard antibiotics in the Lao PDR

Abstract: Objectives In 2012, a stratified random survey, using mystery shoppers, was conducted to investigate the availability and quality of antibiotics sold to patients in the private sector in five southern provinces of the Lao People’s Democratic Republic (Laos). Methods A total of 147 outlets were sampled in 10 districts. The active pharmaceutical ingredient (API) content measurements for 909 samples, including nine APIs (amoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Although P. aeruginosa is considered to be intrinsically resistant to tetracycline (Morita et al ., 2001), thence this antimicrobial is not of choice when it comes to therapies, prior works have revealed this antibiotic to be present in substantial amounts in natural habitats (Ok et al ., 2011; Hou et al ., 2016; Rodriguez‐Mozaz et al ., 2020). In addition, there exists evidence of substandard tetracycline usage – which does not have the stated quantity of API – in developing countries (Johnston and Holt, 2014; Tabernero et al ., 2019). Further, we have previously shown that tigecycline, an antibiotic to which P. aeruginosa is intrinsically resistant too, selects for mutants displaying cross‐resistance to clinically useful antibiotics (Sanz‐Garcia et al ., 2018a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although P. aeruginosa is considered to be intrinsically resistant to tetracycline (Morita et al ., 2001), thence this antimicrobial is not of choice when it comes to therapies, prior works have revealed this antibiotic to be present in substantial amounts in natural habitats (Ok et al ., 2011; Hou et al ., 2016; Rodriguez‐Mozaz et al ., 2020). In addition, there exists evidence of substandard tetracycline usage – which does not have the stated quantity of API – in developing countries (Johnston and Holt, 2014; Tabernero et al ., 2019). Further, we have previously shown that tigecycline, an antibiotic to which P. aeruginosa is intrinsically resistant too, selects for mutants displaying cross‐resistance to clinically useful antibiotics (Sanz‐Garcia et al ., 2018a).…”
Section: Resultsmentioning
confidence: 99%
“…This result exemplifies the possibility of selecting resistance to antibiotics of clinical relevance even in environments not polluted by them, as a consequence of cross‐selection processes. Besides these non‐clinical situations, it should not be disregarded that, in certain regions, poor‐quality medicines, which harbour a substandard quantity of API, are being used in clinics, being precisely the case of ciprofloxacin and tetracycline (Johnston and Holt, 2014; Frimpong et al ., 2018; Tabernero et al ., 2019). Then, this reality enlarges the variety of circumstances under which AR selection mediated by low antimicrobial concentrations could be befalling.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most commonly reported substandard, falsified, and unregistered medicines are antibiotics, antimalarial, anthelmintic, and antiprotozoal medicine. Antihypertensive medicines are also exposed to this problem (Chikowe et al, 2015 ; Hambisa et al, 2019 ; Kitutu, 2015 ; Koech et al, 2020 ; Njeri et al, 2021 ; Oli et al, 2020 ; Osei-Safo et al, 2014 ; Ozawa et al, 2018 ; Patricia et al, 2019 ; Visser et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another unresolved issue is that in many low-income and middle-income countries, treatment of TB is left to the private sector,79 risking fuelling the MDR-TB epidemic by increasing inappropriate and indiscriminate antimicrobial use80 81 as medicines may be sold loose with no labelling or manufacturing information 82…”
Section: Discussionmentioning
confidence: 99%
“…78 Another unresolved issue is that in many low-income and middle-income countries, treatment of TB is left to the private sector, 79 risking fuelling the MDR-TB epidemic by increasing inappropriate and indiscriminate antimicrobial use 80 81 as medicines may be sold loose with no labelling or manufacturing information. 82 Initiatives to improve medicine procurement as a means of reducing TB drug SF burden includes The WHO Prequalification of Medicines Programme, set up in 2001 to facilitate access to medicines that meet unified standards of quality, safety and efficacy. In 2023, 125 finished TB products were included in the list.…”
Section: Bmj Global Healthmentioning
confidence: 99%